Optical spectroscopic and electrochemical characterization of oxide films on a ferritic stainless steel. Issue 3 (14th January 2020) - Fan, Changfeng; Shi, Jianmin; Sharafeev, Azat; Lemmens, Peter; Dilger, Klaus
Abstract: Colored oxide films that form on ferritic stainless steel in a high‐temperature, oxidizing environment and correspond to different chemical compositions can cause a deterioration of pitting resistance and corrosion performance. Herein, optical spectroscopic and electrochemical techniques have been used to reveal the relationship between color, chemical composition, and corrosion resistance of oxide films formed in the temperature range from 400°C to 800°C for 30 min and at 800°C for 10, 20, 30, and 60 min. The substrate with a thin and dense passivation film leads to a low pitting potential but high corrosion resistance. Oxide films of yellowish or brownish color formed below 600°C are mainly iron oxides, which correspond to low corrosion resistance. No passivation characteristics can be observed for polarization curves of oxide films formed at 500°C and 600°C. The color of oxide films varies from blue to dark gray with the increase of oxidation time at 800°C. Corrosion resistance changes with different proportions of Fe3 O4, Cr2 O3, and FeCr2 O4 . The gray oxide films formed at 800°C for 30 min exhibit the lowest pitting susceptibility and the highest corrosion resistance. Abstract : Surface characteristics and chemical compositions of oxide films on ferritic stainless steel were studied by optical spectroscopic measurements. Corrosion properties were investigated by cyclic polarization and electrochemical impedance spectroscopy. A correlation between thermal colors, chemical compositions, and electrochemical parameters was established with the aim of shedding light on the effect of oxidation on the corrosion behavior of ferritic stainless steel.